Mapping Body, Gender, and Sexuality in Queer Studies - Wijaya, Hendri Yulius (Jurnal Perempuan, 2015)
This paper examines the complexities of human sexuality by challenging asumptions that have been built on binarism and biological-determinism. This attempt is done by examining the development of sexuality theory and studies from feminism to queer theory, through the lens of some theorists, from Michel Foucault, Judith Butler, Jack Halberstam, to Sara Ahmed. In addition, the development of sexuality studies in Indonesia is also explored, in order to show a myriad of interactions and relations of knowledge between global and local. Queer theory also provides space to criticize the hegemony of existing ‘labels’ which are originated from the West, and also to show that the meaning and subjectivity shaped by these labels are not always fixed when they are transferred to Indonesian context. For above reasons, this paper introduces the theoretical concept of sex(t)uality—in which sexuality operates like text.